2017
DOI: 10.3906/tar-1612-30
|View full text |Cite
|
Sign up to set email alerts
|

Pokeweed (Phytolacca americana L.) antiviral protein inhibits Zucchini yellow mosaic virus infection in a dose-dependent manner in squash plants

Abstract: Pokeweed antiviral protein (PAP) of Phytolacca americana L. (pokeweed) is a single-chain ribosome-inactivating protein (RIP) characterized by its ability to depurinate plant ribosomes. Here, we isolated, cloned, and expressed the ribosome inactivating protein (RIP) gene, designated as pokeweed antiviral protein type 1 (PAP I), from the summer leaves of pokeweed collected from the Black Sea region (Turkey). Our findings presented here provide direct evidence that exogenous application of PAP I causes concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Further studies suggested that the exogenous application of PAP appears to enhance the systemic resistance of N. benthamiana to TMV infection ( Zhu et al, 2016 ). Application of PAP I also causes concentration-dependent inhibition of zucchini yellow mosaic virus (ZYMV) infection on squash plants ( Sipahioğlu et al, 2017 ). Dianthins isolated from the leaves of Dianthus caryophyllus mixed with TMV strongly decreased the amount of local lesions on plant leaves of Nicotiana glutinosa ( Stirpe et al, 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies suggested that the exogenous application of PAP appears to enhance the systemic resistance of N. benthamiana to TMV infection ( Zhu et al, 2016 ). Application of PAP I also causes concentration-dependent inhibition of zucchini yellow mosaic virus (ZYMV) infection on squash plants ( Sipahioğlu et al, 2017 ). Dianthins isolated from the leaves of Dianthus caryophyllus mixed with TMV strongly decreased the amount of local lesions on plant leaves of Nicotiana glutinosa ( Stirpe et al, 1981 ).…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of antiviral activity has been done by counting the number of lesions [ 88 , 93 ], the time of onset of symptoms [ 77 , 79 ], the number of infected plants [ 105 ], or the severity of the infection symptoms [ 78 , 115 ]. Virus levels have also been estimated by ELISA [ 99 ], Western blotting analysis [ 81 ], RT-PCR analysis [ 101 ], quantitative real-time PCR analysis [ 81 , 82 ], electron microscopy [ 92 ], or by determining the infection capacity of an extract from the infected plant [ 92 ]. Another approach has been the construction of virus-resistant transgenic plants [ 80 , 102 ].…”
Section: Activity Against Plant Virusesmentioning
confidence: 99%
“…Çizelge 1 Tip1 Ribozom inaktive eden proteinlere örnekler (Hong et al, 1996;Balasaraswathi et al, 1998;Stirpe, 2004;Picard et al, 2005;Sipahioğlu et al, 2017…”
Section: Rip'lerin Sınıflandırılmasımentioning
confidence: 99%
“…Aynı yöntemle üretilen ve saflaştırılan PAP I proteini, kabak bitkisi yapraklarına harici olarak düzenli biçimde uygulandığında 2 μg/ml konsantrasyonunun Zucchini yellow mosaic virus (ZYMV) infeksiyonunu engellediği görülmüştür. Tek başına uygulandığında, purifiye PAP I'in aynı zamanda bitkilerde cüceleşmeye neden olduğu rapor edilmiştir (Sipahioğlu et al, 2017).…”
Section: Rip'lerin Bitki Virüs Hastalıklarının Kontrolünde Kullanılmaunclassified